Textile and Chemical Subsectors in the Azerbaijani Economy: A Descriptive Glance at Possible De-Industrialization - Ibrahim Niftiyev (SSRN, 2022)
Azerbaijan's economy has been investigated within Dutch disease (DD) and Natural Resource Curse Theory (NRCT) several times during the last 20-22 years, but the studies relied on heavily aggregated data and speculative theoretical models. Opinions differ in academia as to how and to what extent these phenomena happened. However, we are still of the assertion that non-oil manufacturing, in general, has experienced adverse effects since the huge oil revenue found its way into the Azerbaijani economy because the cost of non-oil production rose and competitiveness declined due to the domestic inflationary pressures. Meanwhile, subsectoral and specific parts of non-oil economy have not been studied in more detail. This working paper invites to consider textile and chemical subsectors as de-industrialized economic subsectors due to the oil boom's take over since 2005 and 2006 in Azerbaijan. The descriptive analysis shows that the textile subsector is less likely to be relevant from a de-industrialization standpoint after the collapse of the Soviet Union; however, certain chemical subsectors seem to strongly react to the oil boom. Still, this does not mean that we have nothing to worry about the output of the textile industry. These results can be supported by quantitative and empirical works, but not limited to. Qualitative methods can generate new insights on microeconomic levels (i.e., factory or industrial park) about non-oil manufacturing in the Azerbaijani economy to reveal potential adverse/positive effects of oil-led economic growth and development. This working paper and upcoming works can be a useful framework for the government officials and decisionmakers to follow more thorough industrial policies to recover non-oil industrial potential of the Azerbaijani economy in a short period.
Keywords: D04; E32; L6; O14; O52; O53; 330; Azerbaijan economy; chemical subsectors; de-industrialization; Dutch disease; economic subsectors; industrial output; natural resource curse theory; non-oil industry; textile subsectors